2017
DOI: 10.1371/journal.pone.0185028
|View full text |Cite
|
Sign up to set email alerts
|

miR-181a decelerates proliferation in cutaneous squamous cell carcinoma by targeting the proto-oncogene KRAS

Abstract: Cutaneous squamous cell carcinoma (SCC) is the second most common human skin cancer with a rapidly increasing incidence among the Caucasian population. Among the many regulators, responsible for cancer progression and growth, microRNAs (miRNA) are generally accepted as key players by now. In our current study we found that microRNA-181a (miR-181a) shows low abundance in SCC compared to normal epidermal skin. In vitro, miRNA downregulation in normal primary keratinocytes induced increased proliferation, while i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Consistently, transgenic mice expressing a dominant Sos1 isoform in the skin showed a hyperproliferative response in keratinocytes in vitro and also in vivo, leading to tissue hyperplasia (22). On the other hand, different bioinformatic tools predict that Sos1 is a putative target gene for miR-181a (27), which is also known to reduce proliferation in primary keratinocytes (28). In this regard, upon Ras elimination, keratinocytes cease proliferation and enter into senescence without any signs of apoptosis induction (19).…”
Section: Discussionmentioning
confidence: 93%
“…Consistently, transgenic mice expressing a dominant Sos1 isoform in the skin showed a hyperproliferative response in keratinocytes in vitro and also in vivo, leading to tissue hyperplasia (22). On the other hand, different bioinformatic tools predict that Sos1 is a putative target gene for miR-181a (27), which is also known to reduce proliferation in primary keratinocytes (28). In this regard, upon Ras elimination, keratinocytes cease proliferation and enter into senescence without any signs of apoptosis induction (19).…”
Section: Discussionmentioning
confidence: 93%
“…A number of previous studies have demonstrated that miRNAs are involved in the pathogenesis of a number of human diseases, particularly different types of cancer ( 12 , 31 , 32 ). Aberrant miRNA expression is frequently observed in cancer, including pancreatic, breast and various types of skin cancer ( 33 35 ). Increasing numbers of miRNAs have been identified as critical regulators in the initiation and progression of cSCC, including miR-1, miR-34a, miR-124 and miR-125b ( 36 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of JNK by galectin-7 [19] Increased keratinocyte differentiation with involucrin expression by oleic acid [20] p63, Skp2 and Msi2 Promotion of cell cycle exit in mouse skin [21] miR-574 ↑ p63 As direct targets of iASPP [22] miR-720 ↑ miR-24 ↑ PAK4 Control of actin cable formation [23] miR-23b-3p ↑ TGIF1 Interference in TGF-β/SMAD signaling [24] miR-378b ↑ NKX3.1 [25] miR-30a ↑ LOX, IDH1, AVEN Barrier function defects in aged epidermis [26] miR-184 ↑ Upregulation of cyclin E and p21 cyclin-dependent kinase inhibitor in a SOCE-dependent manner [27] miR-181a ↑ cell differentiation under high calcium or UVA exposure [28,29] miR [33] miRNAs targeted by p63 miR-34a ↑ SIRT6 miR-34a and miR-34c as direct targets of p63 [34,35] miR-34a ↑ KLK4 Induction of a senescent phenotype in keratinocytes [36] ↑: upregulation (increase), ↓: downregulation (decrease).…”
Section: Snai2 and ∆Np63mentioning
confidence: 99%
“…Substantial data associated with miRNAs, either upregulated or downregulated, and keratinocyte proliferation have been reported in psoriasis. The downregulated miRNAs include miR-125b, miR-181b-5p, miR-520a, miR-194, miR-217, miR-138, miR-320b, miR-150, miR-145-5p, miR-20a-3p, miR-876-5p, miR-99a, miR-187, miR-548a-3p, miR-330, and miR-146a AKT3 [47] miR-181b-5p AKT3, TRL4 [47,48] miR-520a AKT [49] miR-320b AKT3 [50] miR-194 GRHL2 [51] miR-217 [52] miR-138 hTERT [53] miR-150 HIF-1α, VEGFA [54] miR-145-5p MLK3 [55] miR-20a-3p SFMBT1 [56] miR-876-5p ANG-1 [57] miR-99a FZD5/FZD8 [58] miR-187 CD276 [59] miR-548a-3p PPP3R1 [60] miR-330 CTNNB1 [61] miR-146a EGFR Psoriasis, cSCC [62,63] miR-96-5p BNP3 Wound healing [64] miR-181a KRAS cSCC [29] miR-99b IGF-1R Condyloma acuminatum [65] miR-203 ∆Np63 Epidermodysplasia verruciformis [66] miR-130a STK40 [79] miR-122-5p SPRY2 [80] miR-223 PTEN [81] miR-17-3p MYOT Wound healing [82] miR-126 PLK2 [83] ↑: upregulation, ↓: downregulation.…”
Section: Keratinocyte Proliferationmentioning
confidence: 99%
See 1 more Smart Citation